DO PRODUTIVISMO À CONSTRUÇÃO DA AGRICULTURA SUSTENTÁVEL: DUAS ABORDAGENS PERTINENTES À QUESTÃO - Teixeira, Olívio Alberto; Lages, Vinícius Nobre (Cadernos de Ciência & Tecnologia, 1996)
Com a idéia de contribuir para a construção de um paradigma sustentável para a agricultura brasileira, acredita-se ser relevante começar com a demonstração dos limites da crise e das conseqüências do tão chamado modelo produtivista, para então apresentar e discutir dois enfoques da questão: por um lado, a construção da noção de agroecologia - seu aparecimento, os obstáculos, limites e as conseqüências no âmbito do desenvolvimento agrícola; por outro, a maneira de entender o desenvolvimento agrícola e rural e de incorporar a problemática do meio ambiente desenvolvido pelo Departamento de Sistemas Agrícolas-SAD, do Instituto Nacional de Pesquisa Agronômica-INRA, na França, e da importância da análise sistêmica neste processo.FROM PRODUCTIVISM TO THE CONSTRUCTION OF SUSTAINABLE AGRICULTURE: TWO APPROACHES RELATED TO THE QUESTION ABSTRACT With the idea of contributing to the construction of a sustainable paradigm for Brazilian agriculture, we believe it to be relevant, beginning with a demonstration of the limits of the crisis and of the consequences of the so-called productivist model, to present and discuss two approaches to the question: on the one hand, the construction of the notion of agroecology – its rise, obstacles, limits, and consequences in the comprehension of agricultural development; and on the other, the manner of understanding agricultural and rural development and of incorporating the environmental problematic developed by the Department of Agrarian Systems and Development–SAD, of the National Institute of Agronomic Research–INRA, in France, and of the importance of systemic analysis in the process.